2017
DOI: 10.1080/15592324.2017.1365214
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through reactive oxygen and nitrogen species is differentially modulated in sunflower seedling root and cotyledon in response to various nitric oxide donors and scavengers

Abstract: Sodium nitroprusside (SNP), diethylenetriamine NONOate (DETA), S-nitroso-n-acetyl-D,L- penicillamine (SNAP), and 4-(p-methoxyphenyl)-1,3,2- Oxathiazolylium-5-olate (CAY) exhibit differential NO releasing ability in aqueous solution and hemoglobin is a more efficient NO quencher than cPTIO in solution. DETA releases 16% more NO compared with SNP in solution. Various NO donors (SNP, DETA, SNAP, and CAY) also bring about a differential but concentration-dependent increase in endogenous NO in seedling cotyledons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In order to deplete endogenous NO, hemoglobin was preferentially used as a NO scavenger over cPTIO on the basis of author's recently published work. 50 We have reported that hemoglobin indeed serves as a very efficient NO scavenger to entrap and scavenge tissue NO from the surface of the sunflower seedling roots even though it is not taken up into the system. In contrast, cPTIO proved to be a very bad choice as NO scavenger.…”
Section: Discussionmentioning
confidence: 98%
“…In order to deplete endogenous NO, hemoglobin was preferentially used as a NO scavenger over cPTIO on the basis of author's recently published work. 50 We have reported that hemoglobin indeed serves as a very efficient NO scavenger to entrap and scavenge tissue NO from the surface of the sunflower seedling roots even though it is not taken up into the system. In contrast, cPTIO proved to be a very bad choice as NO scavenger.…”
Section: Discussionmentioning
confidence: 98%
“…Oxygenated hemoglobin (HbO 2 ) is considered as a good choice, and can effectively scavenge NO within concentration range from 125 to 500 µM from both sunflower seedling roots and cotyledons tissue homogenates [21]. The reaction between NO and HbO 2 is rapid, stoichiometric and leads to formation of methemoglobin and nitrate (NO 3− ) [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reliable substitute NO quencher is required for various applications. Our recently published observations provided some evidence for the probable role of hemoglobin added in the growth medium on its ability to quench endogenous NO in sunflower seedlings [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…GB maintains the equilibrium of K + ions by suppressing Na + uptake through apoplastic route and thus, alleviating stress. [24][25][26] Based on already standardized concentrations of NaCl (120 mM), diethylenetriamine (DETA; 250 μM), and diethyldithiocarbamate (DETC; 250 μM) in the author's laboratory, 27 the present work focuses on examining photomodulation of GB homeostasis, 28,29 as a long-distance signaling response to salt stress in sunflower seedling cotyledons. Modulation of BADH activity 30,31 and transcript 31 levels by nitric oxide (NO) has been proposed to be differentially regulated in light-and dark-grown seedlings, thereby altering GB homeostasis.…”
Section: Introductionmentioning
confidence: 99%